Human trafficking as a racialized economy and the exploitation of indigenous socio-spatial (im)mobility in North America - Hill, Margo; Anderson, Matthew B.; King, Idella (Frontiers in Sustainable Cities, 2022)
The phrase “missing and murdered indigenous women” (MMIW) refers to the hundreds of deaths and disappearances of Native American women that occur each year. A growing human and sex trafficking industry that exploits indigenous women as forced sex workers is causing these numbers to increase year after year. Traffickers actively target tribal communities due to the increased likelihood of not being caught or prosecuted by an unjust legal-jurisdictional system that effectively invites traffickers onto Native American reservations. The disproportionate risks facing Native American women are a direct consequence of the now well documented historical injustices experienced by indigenous communities since contact with European colonists. Although scholarship on MMIW is growing, little attention has focused on the unique socio-spatial dynamics related to Native American (im)mobility patterns and the ways in which these dynamics enhance vulnerability to victimization by traffickers. This study empirically unpacks these dynamics in the context of North America. In the process, the industry that profits on trafficking indigenous women is conceptualized as a “racialized economy” that is constituted through an exploitative relationship between the city (the market for trafficked indigenous sex slaves) and the reservation. Here, the reservation becomes a virtual extension of the city, a relational understanding that foregrounds the urban dimension to this problem. We conclude by discussing how this analysis informs best practices that can be employed to mitigate against these (im)mobility-related risk factors and save lives.